Exploring Indonesian English Teachers’ Perspectives toward the Use of Translation in English Language Teaching (ELT) Classroom - Saputra, Nizar (Universitas Malikussaleh, 2020)
This study aims to investigate Indonesian teachers' perspectives of translation or first language used in ELT classrooms as well as to find out the teachers' strategies on how to incorporate translation as their pedagogical tool. This research is applied in a case study methodology, in which the researcher interviewed three English teachers in Indonesia to explore their perspectives. The raw data was analysed by using thematic analysis to find the emerging themes of the interview data which led to the result of this qualitative research. The result of the finding indicates that the teachers mostly have positive perceptions about TILT (translation in language teaching). Most participants believed that when translation use selectively, it can help students with foreign language learning, promote students' metalinguistic awareness, function as a thinking tool, mediate social interaction, and function as social mediation. Additionally, the strategies of TILT applied by the teachers in this study entail explaining difficult concepts and grammar, avoiding chunks of word translation, and nurturing students’ critical thinking and problem-solving skills. It is suggested that if translation is integrated into language teaching, it should be used selectively as a pedagogical tool to support students’ learning.